Impact on Reliability in the Control-Flow of Programs under Compiler Optimizations - Parizi, Rafael; Ferreira, Ronaldo; Freitas, Álvaro; Carro, Luigi (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2012: Anais do II Simpósio Brasileiro de Engenharia de Sistemas Computacionais, 2012)
This paper evaluates the impact on reliability in the control-flow of programs that compiler optimizations incur in terms of fault coverage for the Automatic Correction of Control-flow Errors technique. This technique was implemented in the LLVM framework, enabling the automated analysis of programs. In order to evaluate the efficiency of the technique of fault tolerance we performed a series of fault injection experiments using the MiBench benchmark suite as case study, measuring how individual and combined optimizations impact reliability.